DEVELOPMENT OF PROJECT ASSESSMENT MODEL FOR MEASURING THE PSYCHOMETRIC ASPECT OF GEOGRAPHY SUBJECT - Wahyuni, Lies; Ruhimat, Mamat (JURNAL PENDIDIKAN ILMU SOSIAL, 2018)
This study aims to 1) identify the various types of assessment project techniques, (2) formulating the measurement instrument in the assessment of the project, (3) develop a model assessment project to measure aspects of psychomotor. The methods used in this research is the study of literature. The results of this research are a model of assessment in the form of matrix flow chart and measurement instruments. The development model has not been conducted product trials. The model is only based on the results of literature study analysis. Then, it becomes a recommendation for further researchers.